Crowd-sourcing (who, why and what). Issue 1 (5th March 2018) - Ikediego, Henry Oluchukwu; Ilkan, Mustafa; Abubakar, A. Mohammed; Victor Bekun, Festus
Abstract : Purpose: There is growing interest in innovative online problem-solving models such as crowdsourcing to serve individuals, firms and the society as a whole. Crowdsourcing is the combination of efforts from various sets of individuals who are either volunteering or working part-time for socioeconomic production, basically in the cyber world. This hybrid work model is already in use by businesses and entrepreneurs; some of the platforms include Amazon mechanical Turk, 99designs, Hit RECORD and Design Crowd. Design/methodology/approach: Much has been parleyed and published, and this is primarily because of the efficient socioeconomic potentials crowdsourcing offers. Findings: This paper addressed the following three questions to help have a better understanding of crowdsourcing: who can perform crowdsourcing? why it is relevant to crowdsource in this present proliferated internet age and if there are going to be some changes in the future and the last but not the least what can be done to promote it in the society? Originality/value: This paper discusses the three W's and concludes with challenges facing the crowdsourcing work model.